Soluble production and function of vascular endothelial growth factor/basic fibroblast growth factor complex peptide. (10th October 2014) - Zhang, Qing; Lao, Xuejun; Huang, Jianhua; Zhu, Zhongsong; Pang, Lei; Tang, Yong; Song, Qifang; Huang, Jiangfang; Deng, Jie; Deng, Ning; Yang, Qin; Sengupta, Aditi M.; et al.
<x xml:space="preserve">Abstract</x> Vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFGF) are important proangiogenic factors in tumor procession. The autocrine and paracrine bFGF and the VEGF in tumor tissue can promote tumor angiogenesis, tumor growth, and metastasis. A VEGF/bFGF Complex Peptide (VBP3) was designed on the basis of epitope peptides from both VEGF and bFGF to elicit in vivo production of anti‐bFGF and anti‐VEGF antibodies. In this study, we reported on the production of recombinant VBP3 using high cell density fermentation. Fed‐batch fermentation for recombinant VBP3 production was conducted, and the production procedure was optimized in a 10‐L fermentor. The fraction of soluble VBP3 protein obtained reached 78% of total recombinant protein output under fed‐batch fermentation. Purified recombinant VBP3 could inhibit tumor cell proliferation in vitro and stimulate C57BL/6 mice to produce high titer anti‐VEGF and anti‐bFGF antibodies in vivo. A melanoma‐grafted mouse model and an immunohistochemistry assay showed that tumor growth and tumor angiogenesis were significantly inhibited in VBP3‐vaccinated mice. These results demonstrated that soluble recombinant VBP3 could be produced by large‐scale fermentation, and the product, with good immunogenicity, elicited production of high‐titer anti‐bFGF and anti‐VEGF antibodies, which could be used as a therapeutic tumor vaccine to inhibit tumor angiogenesis and tumor growth. © 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:194–203, 2015